Analytic Univalent fucntions defined by Gegenbauer polynomials - Sunday Olatunji (Journal of Mahani Mathematical Research, 2023)
The numerical tools that have outshinning many others in the history of Geometric Function Theory (GFT) are the Chebyshev and Gegenbauer polynomials in the present time. Recently, Gegenbauer polynomials have been used to define several subclasses of an analytic functions and their yielded results are in the public domain. In this work, analytic univalent functions defined by Gegenbauer polynomials is considered using close-to-convex approach of starlike function. Some early few coefficient bounds obtained are used to establish the famous Fekete-Szego inequalities.